PHILOSOPHICAL-CULTURAL CONCEPTION OF TELEVISION AS A VISUAL PRACTICES OF XX-XXI CENTURY - A. M. Tormakhova (Antropologìčnì Vimìri Fìlosofsʹkih Doslìdžen')
Purpose of the article is to analyze the philosophical and cultural ideas about television, which is a leading visual practice of XX century. It does not lose its relevance in the beginning of the XXI. The role of television lies in visual presentation and formation of the basic norms of taste and traditions of different social groups. Television is the leading communicative practice, which consideration is represented differently in modern science. Research methodology involves an appeal to the philosophical and cultural concepts, representing different approaches to the understanding of television. The paper considers the views of Western scholars, such as R. Arnheim, M. Wolff, A. Kroker, G. Lipovetsky, M. McLuhan, D. Mulvin, J. Mittell, N. Postman, L. Saffhil, J. Sterne, E. Thompson, J. Fiske, S. Shapiro. During analysis of the issue of the specific nature of television content the works of Russian scientists – T. Savitskaya, N. Samutina and Polish contemporary author – R. Sapenko were used. Originality lies in the depiction of the main approaches to the study of television as a visual communicative practice. Deployment of the author's position within the designated issues is presented as a historical digression – from the first attempts at understanding the phenomenon of television to the newest scientific theories that have found expression in contemporary American philosophical and cultural thought. Results of the study can be used in the training course "Visual communication and practices." Conclusions indicated that the majority of contemporary visual practices based on certain patterns, embedded TV. Despite the emergence of new media practices, TV does not lose relevance, everywhere present in the culture, which means that his research will allow a better understanding of the specificity of cultural creativity process.